Labor Supply and Matching Rates for Welfare Recipients: An Analysis Using Neighborhood Characteristics - Bas van der Klaauw; Jan C. van Ours (Institute for the Study of Labor (IZA), 2000)
This paper investigates how in addition to personal characteristics the neighborhood affects the individual transition rate from welfare to work. We use a unique administrative database on welfare recipients in Rotterdam, the second largest city of The Netherlands. We find that the exit rate to work of young Dutch welfare recipients is influenced by the neighborhood unemployment rate. Other neighborhood characteristics such as the average housing price are not important. From this we conclude that for young Dutch welfare recipients a high local unemployment rate has a negative spillover effect on the transition from welfare to work.
Keywords: J64; C41; 330; Welfare to work; unemployment duration; spillovers; Sozialhilfeempfänger; Arbeitsangebot; Arbeitslosigkeit; Nachbarschaftsökonomie; Rotterdam